The Effects of Covert Narcissism on Chinese College Students Cyberbullying: The Mediation of Hostile Attribution Bias and the Moderation of Self-Control - Fang X; Zhang K; Chen J; Chen M; Wang Y; Zhong J (Psychology Research and Behavior Management, 2023)
Xiaohong Fang,1 Kai Zhang,1 Jie Chen,1 Meitao Chen,1 Yanyan Wang,1 Jianping Zhong2 1School of Education, Huaibei Normal University, Huaibei, People’s Republic of China; 2School of Humanities and Education, Foshan University, Foshan, People’s Republic of ChinaCorrespondence: Kai Zhang, School of Education, Huaibei Normal University, Huaibei, Anhui, 235000, People’s Republic of China, Tel +86 15856116221, Email zhangkaitop@163.comPurpose: The prevalence of cyberbullying has increased along with the growth of social media, which has brought about many adverse effects on individual development. The current study aimed to explore the connection between covert narcissism and cyberbullying and to test the roles of hostile attribution bias and self-control in the relationship between covert narcissism and cyberbullying.Materials and Methods: A total of 672 Chinese college students filled up questionnaires measuring covert narcissism, cyberbullying, hostile attribution bias, and self-control.Results: The results indicated that covert narcissism positively and significantly predicted cyberbullying. Hostile attribution bias partially mediated the relationship between covert narcissism and cyberbullying. Additionally, self-control moderated the relationship between covert narcissism and cyberbullying. Specifically, the positive predictive effect of covert narcissism on cyberbullying gradually weakened as self-control improved.Conclusion: This study explored the underlying mechanism of cyberbullying and found that covert narcissism could affect cyberbullying through hostile attribution bias. Self-control moderated the relationship between covert narcissism and cyberbullying. The results have significant implications for the intervention and prevention of cyberbullying and additional evidence for the relationship between covert narcissism and cyberbullying.Keywords: covert narcissism, cyberbullying, hostile attribution bias, self-control, college students